أثر التغير الاجتماعي على لباس المرأة الجزائرية - شوشة نسيمة (جامعة البليدة2- كلية العلوم الإنسانية والإجتماعية, 2026)
تسعى هذه الدراسة الى البحث في أثر التغير الاجتماعي على لباس المرأة في الأغواط من منظور انثروبولوجي، مركزة على تغير أنماط اللباس من التقليدية الى الحديثة، وما تبعه من تحول على مستوى وظائف ودلالات اللباس في الممارسات اليومية، الاحتفالية والطقوسية، بفعل جملة من العوامل التاريخية الممثلة في الاستعمار، الاستقلال ،الأحداث التي عرفتها الجزائر بداية من نهاية الثمانينات، الى جانب تمكين المرأة من خلال التعليم والعمل، اين يتم تفسير التغير في إطار بنيوي وظيفي، وضمن الاتصال الثقافي وعمليات التثاقف والتقليد، كما تسعى الى البحث في الدور الذي لعبته الأعراف، القيم، المعتقدات والسلطة المجتمعية في تشكيل نظام لباس المرأة في الاغواط وظهورها في الفضاء العام عبر مختلف الفترات التاريخية، ومن هذا المنطلق اعتمدت الدراسة على المنهج التاريخي والاثنوغرافي، وعلى تقنية المقابلة والملاحظة لجمع المعطيات، بينما تم توظيف التحليل السيميائي لتحليل دلالات اللباس، وبهدف السعي لجمع عناصر اللباس التقليدي وتوثيقها وتتبع تغيرها تم الاعتماد على عينة ممثلة من فئات جيلية مختلفة الخصائص، وخلصت الدراسة الى أن جميع أنماط اللباس التي عرفتها المرأة في الأغواط مثلت أنظمة دلالية متعدد المعاني، أين عكس التغير في هذا النظام تغيرات أعمق في البنية الاجتماعية ككل، طالت القيم والأعراف الاجتماعية المحددة لمعايير لباس المرأة، وعلاقات الهيمنة والسلطة الأبوية، وأخيرا تغير الأدوار الاجتماعية للمرأة، الأمر الذي فسر تراجع الأنماط التقليدية للتعبير عن الهوية الثقافية، أمام هيمنة الأنماط العصرية المعبرة عن الهوية الفردية للمرأة في سياق This study seeks to examine the impact of social change on women’s dress in Laghouat from an anthropological perspective, focusing on the transformation of clothing styles from traditional to modern and the subsequent shifts in the functions and meanings of dress within everyday, festive, and ritual practices, These changes were driven by a set of historical factors, including colonialism, independence, the Islamic revival, in addition to the empowerment of women through education and employment. The study interprets these transformations within a structural-functional framework and in relation to cultural contact, processes of acculturation, and imitation. It also explores the role played by customs, values, beliefs, and social authority in shaping women’s dress systems in Laghouat and their appearance in public space across different historical period, Methodologically, the study draws on historical and ethnographic approaches, employing interviews and observation to collect data, while semiotic analysis was used to uncover the meanings embodied in clothing. To document elements of traditional dress and trace their transformations, the study relied on a representative sample spanning different generational groups. The findings reveal that the various dress styles adopted by women in Laghouat constitute multilayered semiotic systems, where transformations in these systems reflect deeper structural changes within society as a whole changes that affected the values and social norms governing women’s dress, relations of power and patriarchal authority, and the shifting social roles of women. These dynamics ultimately explain the decline of traditional forms of dress as markers of cultural identity in favor of modern styles that express women’s individual identities within a contemporary context.
المرأة الأغواطية أنموذجا
Keywords: التغيير الإجتماعي; المجتمع الجزائري; المرأة والتغيير الإجتماعي; لباس المرأة الجزائرية